Verticillium wilts - Pegg, G. F. 1930- (CABI, 2002)
This book considers the pathogenic wilt-inducing Verticillium spp. under the following headings: Taxonomy, Morphogenesis and Morphology, Cytology and Genetics, Aetiology, Ecology, Physiology and Metabolism, Pathogenesis, Resistance, Control (physical, chemical, biological, integrated legislation and quarantine, and resistance breeding), Hosts, and Techniques and Methodology. The book aims to produce in one volume a discursive compendium of information on Verticillium to enable young (and older) research workers to see what has already been achieved and to identify the many new areas of research in which original contributions could be made to future our understanding and control of this most important pathogen and its diseases.